Perancangan Model Inovasi Pembelajaran Menggunakan Metode Multimedia Development Life Cycle (MDLC) Berbantu Teknologi Platform Lumi - Gama Edo, Stanislaus; D.I. Mau, Stefanus; Purnami Setiawi, Agustina (JOURNAL OF ELECTRICAL AND SYSTEM CONTROL ENGINEERING, 2024)
This research was carried out with the aim of designing interactive multimedia introductory media using digital-based App applications. The method used in this research is the Multimedia Development Life Cycle (MDLC) method. MDLC consists of 6 stages, namely concept, design, material collection, assembly (manufacture), testing (testing) and distribution. After the design process is complete, the next step is validation testing of the media and materials to determine the suitability of the designed media. These results show the results of the design made, in this application the output is HTML, which can be opened on all devices without installing other applications and only requires a Chrome browser or other browser. Then later on in the final result there will be a determination of the score from the correct and incorrect results. Conclusion: The introduction of the learning innovation model implemented in Natural Sciences lessons has taken nine development steps from Borg and Gall, namely: (a) research and data collection, (b) planning, (c) initial product development, (d) field trials initial, (e) revising the product, (f) field trials.